Islamic Spirituality based Self-guidance Model for Managing Stress among Working College Students - Dzikra, Olyvia Chairunnisa; Umayah, Umi; Meidyansyah, Rinaldi; Zubaidah, Zubaidah; Adam, Yasin; Iloakasia, Adaobi Jennifer (Program Studi Bimbingan dan Konseling Islam, 2025)
Stress among working students arises due to the dual demands of academic and professional responsibilities. This study aimed to explore the role of Islamic spirituality in managing stress among working students. The research approach used a qualitative phenomenological method involving in-depth interviews with five working college student participants. Data were analysed using thematic analysis to identify patterns in their experiences. The results showed that Islamic spiritual practices such as prayer, supplication, remembering Allah Swt (dhikr), and understanding concepts such as tawakal and qadar play an important role in reducing stress, increasing inner peace, mental resilience and optimism in the face of academic and professional pressures. In addition, support from the Muslim community also contributes to lowering anxiety and motivating them to overcome challenges. This study concludes that Islamic spirituality is an effective coping strategy for working university students in managing stress. The findings enrich the existing literature on the relationship between spirituality and stress management and offer practical implications for educational institutions to design holistic support programs that help students maintain academic, professional, and mental well-being.